Umaga na, tala - Molina, Russell; Nada, Marcus; Tamayo, Faith (Quezon City LG & M Corporation, 2013)
Umaga na, tala entwines the lives of a little star in the sky and a little boy on earth in a moving tale about one's sense of purpose and responsibility.
"Ages 7-13 y.o."
Text in English and Filipino.
Keywords: Stars -- Juvenile literature; Children's stories, Philippine (English)